Non-monotonic size dependence of diffusion and levitation effect: a mode-coupling theory analysis - Nandi, Manoj Kumar; Banerjee, Atreyee; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2013)
We present a study of diffusion of small tagged particles in a solvent, using mode coupling theory (MCT) analysis and computer simulations. The study is carried out for various interaction potentials. For the first time, using MCT, it is shown that only for strongly attractive interaction potential with allowing interpenetration between the solute-solvent pair the diffusion exhibits a non-monotonic solute size dependence which has earlier been reported in simulation studies [P. K. Ghorai and S. Yashonath, J. Phys. Chem. B 109, 5824-5835 (2005)]. For weak attractive and repulsive potential the solute size dependence of diffusion shows monotonic behaviour. It is also found that for systems where the interaction potential does not allow solute-solvent interpenetration, the solute cannot explore the neck of the solvent cage. Thus these systems even with strong attractive interaction will never show any non-monotonic size dependence of diffusion. This non-monotonic size dependence of diffusion has earlier been connected to levitation effect [S. Yashonath and P. Santikary, J. Phys. Chem. 98, 6368 (1994)]. We also show that although levitation is a dynamic phenomena, the effect of levitation can be obtained in the static radial distribution function. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4796232]